Analysis of Food Security of Farm Households in the Dodokan River Watershed Area, Lombok Island - Bandrang, Danu Dayako; Sa'diyah, Halimatus; Suparmin; Halil; Abdurrahman, Muktasam; Husni, Syarif (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The research aims to determine the level of food security and the factors that influence the level of food security of farming households in the Dodokan watershed. The topography of the watershed from upstream to downstream certainly influences the water supply in each part of the watershed, namely in the upstream, middle and downstream parts, which has implications for the way farmers carry out business on the land they work on, both cropping and cropping patterns. This of course raises the assumption that farmers in upstream and middle areas will be more prosperous because of a better supply of natural resources and whether this will have an impact on production levels and income of farmer households. This research used a household survey of 68 farmers selected using proportional sampling. Cross-classification between expenditure and portion of household energy adequacy levels is used to answer the first objective. The ordinal logistic model is used to answer the second objective. The results of the research show that 27.94% of farmer households have achieved food security levels, 30.88% have less, 38.24% are vulnerable, and 2.94% have food insecurity. Based on the results of ordinal logistics testing, household food security is positively influenced by household income, number of household members, household expenditure and negatively by the housewife's education.